Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/oncotarget.12537
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of long non-coding RNA in breast cancer: an overview of mechanism and clinical implication

Abstract: Long non-coding RNAs (lncRNAs), which occupy nearly 98% of genome, have crucial roles in cancer development, including breast cancer. Breast cancer is a disease with high incidence. Despite of recent progress in understanding the molecular mechanisms and combined therapy strategies, the functions and mechanisms of lncRNAs in breast cancer remains unclear. This review presents the currently basic knowledge and research approaches of lncRNAs. We also highlight the latest advances of seven classic lncRNAs and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 123 publications
2
60
0
1
Order By: Relevance
“…Based on length, ncRNAs can be divided into short ncRNA (miRNA, siRNA and piRNA) and long ncRNA (lncRNA) (10). Aberrant expression of several lncRNAs has been reported in human diseases, including breast cancer (11,12). However, the number of lncRNAs that have been experimentally identified as oncogenes or tumor suppressors in breast cancer is considerably low (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Based on length, ncRNAs can be divided into short ncRNA (miRNA, siRNA and piRNA) and long ncRNA (lncRNA) (10). Aberrant expression of several lncRNAs has been reported in human diseases, including breast cancer (11,12). However, the number of lncRNAs that have been experimentally identified as oncogenes or tumor suppressors in breast cancer is considerably low (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-21, miR-124, miR-148a and miR-384 have been reported to be involved in the progression of HCC (17)(18)(19)(20). In recent years, emerging studies showed that aberrant expression of long noncoding RNAs (lncRNAs), a class of ncRNAs more than 200 nucleotides in length, was involved in the tumorigenesis and development of various cancer, including HCC (21)(22)(23)(24). Present research demonstrated that lncRNA function as competing endogenous RNAs (ceRNAs) or act as molecular 'sponges' to regulate the concentration, expression and biological functions of miRNAs (25).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there remains a considerable need for identification of novel biomarkers and better understanding of the molecular mechanisms underlying breast cancer. So far, several lncRNAs have been reported to show different expression patterns and be closely associated with breast cancer . For example, HOTAIR expression is increased in both primary breast tumours and metastases and can significantly predict subsequent metastasis and death of breast cancer .…”
Section: Discussionmentioning
confidence: 99%